A risk management perspective on macroprudential policy - Sulkhan Chavleishvili; Stephan Fahr; Manfred Kremer; Simone Manganelli; Bernd Schwaab (European Central Bank (ECB), 2021)
Macroprudential policymakers assess medium-term downside risks to the real economy arising from financial imbalances and implement policies aimed at managing those risks. In doing so, they face an inherent intertemporal trade-off between the expected growth and downside risks. This paper reviews the literature on Growth-at-Risk, embeds it in the wider literature on macroprudential policy, and proposes an empirical risk management framework that combines insights from the two literatures, by forecasting the entire real GDP growth distribution with a structural quantile vector autoregressive model. It accounts for direct and indirect interactions between financial vulnerabilities, financial stress and real GDP growth and allows for potential non-linear amplification effects. The framework provides policymakers with a macro-financial stress test to monitor downside risks to the economy and a macroprudential stance metric to quantify when interventions may be beneficial.
Keywords: G21; C33; 330; Growth-at-risk; stress testing; quantile vector autoregression; financial conditions; macroprudential policy